Bungeanum Improves Cognitive Dysfunction and Neurological Deficits in D-Galactose-Induced Aging Mice via Activating PI3K/Akt/Nrf2 Signaling Pathway - Zhao, Meihuan; Tang, Xueqian; Gong, Daoying; Xia, Peng; Wang, Fushun; Xu, Shijun (Frontiers in Pharmacology, 2020)
Zanthoxylum bungeanum Maxim, (Rutaceae), a popular condiment and dietetic herbal medicine, has been traditionally used in the treatment of forgetfulness, as recorded in "Shen Nong's Herbal Medicine", an old Chinese Medicine book. To explore effects and potential mechanisms of it, extracts of Z. bungeanum through water (WEZ), volatile oil (VOZ), petroleum ether (PEZ) and methylene chloride (MCZ) were used to treat the memory loss induced in D-galactose induced aging mice. The impaired memory was significantly alleviated after WEZ and VOZ extracts treatment. WEZ and VOZ extracts also prevented D-galactose-induced hippocampal neuron damage. In addition, WEZ and VOZ extracts upregulated Nrf2 and HO-1, which suggests that the effects of WEZ and VOZ extracts on oxidative stress and apoptosis might be involved in the cognitive dysfunctions. Furthermore, WEZ and VOZ extracts enhanced the activation of PI3K/Akt, which suggests that Z. bungeanum has an appreciable therapeutic effect on learning and memory disabilities and its mechanism may be related to activate PI3K/AKT signaling pathway. Collectively, our study suggested that Z. bungeanum extracts are promising agents for prevention of aging-related cognitive dysfunction and neurological deficits.